Early photoreceptor assessment as a predictor for visual acuity gain after vitrectomy for macula-off retinal detachment - Lourdes Vidal-Oliver; Jorge Mataix-Boronat; Margot Mangen; Enrique Alfonso-Muñoz; Elena Palacios-Pozo; M. Jesus López-Prats; Carmen Desco (International Journal of Retina and Vitreous)
Abstract Background Visual recovery after macula-off rhegmatogenous retinal detachment (RRD) remains limited in many cases, largely due to photoreceptor damage. This study aimed to assess the predictive value of early outer retinal findings on optical coherence tomography (OCT) for visual acuity outcomes. Methods A retrospective, longitudinal study was conducted on 106 eyes with macula-off RRD treated with vitrectomy and gas tamponade. The primary outcome was best-corrected visual acuity (BCVA) at six months postoperatively. Predictive variables included ellipsoid zone (EZ) and external limiting membrane (ELM) integrity, relative EZ reflectivity (rEZR) at one month, as well as age, time to surgery, macular status, baseline BCVA, and RRD extension. Associations were analyzed using linear regression models. Results One-month ELM and EZ integrity were independent predictors of six-month BCVA after adjusting for rEZR and baseline LogMAR BCVA (ELM absence: ß=0.33; EZ absence: ß=0.20; both p < 0.04). rEZR increased significantly between one and six months (p < 0.05), stabilizing thereafter, and moderately correlated with BCVA (r=-0.6). Other variables were not significant in univariate analysis and were excluded from the multivariate model. Conclusions Absence of the ELM at one month indicates poor visual prognosis, corresponding to an estimated four-line visual loss. rEZR may serve as a sensitive marker of photoreceptor metabolic recovery. These findings support the development of imaging-based deep learning models for visual outcome prediction in macula-off RRD.